APPLICATIONS OF VIRTUAL REALITY TECHNOLOGY IN PSYCHIATRY – A REVIEW - Rybicki, Wiktor; Dutczak, Radosław; Sobieska, Aleksandra; Korpacka, Alicja; Mularczyk, Patrycja; Okoń, Mateusz; Lecyk, Zuzanna; Gawlik, Alicja; Lubowiecka, Małgorzata (International Journal of Innovative Technologies in Social Science, 2026)
Virtual reality (VR) is a promising tool supporting diagnostics and therapy in psychiatry, aligning with the Health 4.0 paradigm of personalized healthcare. This review synthesizes the available scientific evidence on VR applications in psychiatry, with particular emphasis on therapeutic mechanisms, clinical effectiveness, and identification of research gaps. The strongest empirical evidence concerns VR exposure therapy (VRET) in the treatment of anxiety disorders, where the effectiveness of VRET is comparable to in vivo exposure (Suso-Ribera et al., 2019). In the case of post-traumatic stress disorder, graded exposure based on the patient’s responses has been shown to be a key moderator of effectiveness, yielding significant therapeutic effects (Heo and Park, 2022). In psychotic disorders, automated VR interventions reduce agoraphobic avoidance (Freeman et al., 2022), while in social phobia, optimal results are achieved by combining VRET with cognitive-behavioral interventions (Tan et al., 2025). The neurobiological mechanisms of therapeutic change are based on amygdala activation and modulation of the medial prefrontal cortex and hippocampus, enabling extinction of the fear response. However, generalization of learned responses beyond the virtual context remains a key challenge (Freeman, 2017). Personalization of interventions using artificial intelligence is in the early stages of development (Bergsnev and Sánchez Laws, 2026). From a clinical perspective, VR is characterized by high acceptability and low dropout rates. Further development of the field requires comparative studies with active interventions, standardization of the sense of presence measurement, and validation of tools for measuring social attitudes toward VR therapy. Integrating VR with traditional therapeutic methods, rather than replacing them, seems to be the most justifiable path forward for this field.